AB0458 Anti-tumor necrosis factor-alpha therapy in refractory behçet uveitis: a single center experience. (23rd January 2014) - Yilmaz, S. G.; Aksu, K.; Keser, G.; Yilmaz, Z.; Sozeri, B.; Ates, H.
Abstract : Objectives: To evaluate the efficacy and safety of anti-tumor necrosis factor-alpha (anti-TNF-α) agents including infliximab (IFX) and adalimumab (ADA) in the treatment of refractory Behcet uveitis. Methods: This retrospective study included 12 cases (M/F:7/5; mean age 31.5 ±9.3 years) with refractory Behçet uveitis with 21 eyes followed up by Ege University Department of Ophtalmology between 2010 and 2012. All the patients fulfilled the international criteria for Behçet's disease (BD). Visual acuity and yearly uveitis relapse rates were evaluated before and after commencement of anti-TNF treatment. Results: Prior to anti-TNF treatment, 6 patients had used conventional immunosuppressive (IS) agents including azathioprine and cyclosporine, and 6 other patients had additionally used interferon-alpha 2a treatment. Before switching to anti-TNF agents, screening for latent tuberculosis was performed using the local guideline. The majority of the patients (n:10) received only IFX infusions 5 mg/kg at 0., 2nd, 6th weeks and in every 8 weeks thereafter. One patient received only ADA subcutaneous injections once in every two weeks, while the other used both agents, i.e. switched from IFX to ADA due to loss of clinical response. Altogether, there were 11 cases who used IFX. Among these cases, infusion periods had to be shortened in 6 cases, in order to control the activity of uveitis. Nevertheless, in three cases, uveitis relapses could not be controlled despite infusions in every four weeks. As mentioned above, one of them was switched to ADA and uveitis activity was controlled, while in two others IFX was stopped due to inefficacy, without having the opportunity of trying another anti-TNF agent. In the remaining single patient who was given only ADA, uveitis was regressed with no relapse. Overall, mean treatment period for anti-TNF agents was 11.6 ± 4.9 (6-21) months, and successful treatment response was observed in 10 out of 12 patients (80%). Considering the 13 eyes of 8 patients who completed one-year period with these anti-TNF agents, basal uveitis relapse rate of 3.4±1.2/year decreased to 0.8±1.0/year (p<0.05). Potential vision was preserved in all of the 21 eyes and visual acuity with Snellen was increased at least two lines in 6 out of 21 eyes (28.6%). In 5 patients who completed the first year of anti-TNF treatment without any relapses, anti-TNF treatment could be stopped only in a single case using ADA, while anti-TNF treatment had to be continued in others. No adverse effect requiring cessation of anti-TNF agents was observed. Conclusions: In line with the previous data, our findings also suggest that IFX and ADA may be tried in the treatment of Behçet uveitis resistant to other therapeutic approaches. Disclosure of Interest: None Declared